2001
DOI: 10.1002/gps.408
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant depressive symptoms and very mild to mild dementia of the Alzheimer type

Abstract: Clinically significant depressive symptoms may be common in individuals with very mild or mild DAT, although they may fluctuate. Information from both a knowledgeable collateral source and the participant is important for detection of depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
0
23
0
1
Order By: Relevance
“…The problem of using a dichotomous variable for complaints of loss of memory has been addressed in the literature (Jonker et al, 1996;Turvey et al, 2000;Wang et al, 2000), and the anxiety disorder and memory loss as a predictor of cognitive declineapproach now is to ask more than one general question or use a more detailed questionnaire. Secondly, researchers (Turvey et al, 2000;Rubin et al, 2001) addressed the problem of using convenience samples that may not reflect true prevalence rates of diseases. However, Zelinski and colleagues (2001) found that there was no difference in representative samples compared to convenience samples, allowing for possible use of convenience samples to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of using a dichotomous variable for complaints of loss of memory has been addressed in the literature (Jonker et al, 1996;Turvey et al, 2000;Wang et al, 2000), and the anxiety disorder and memory loss as a predictor of cognitive declineapproach now is to ask more than one general question or use a more detailed questionnaire. Secondly, researchers (Turvey et al, 2000;Rubin et al, 2001) addressed the problem of using convenience samples that may not reflect true prevalence rates of diseases. However, Zelinski and colleagues (2001) found that there was no difference in representative samples compared to convenience samples, allowing for possible use of convenience samples to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…5,31,32 Major depression is common among patients with probable Alzheimer disease, especially those with mild and moderate dementia, but is less common in severe Alzheimer disease. 28,45,46 Other authors have reported that approximately 33% to 60% of older adults with moderate levels of cognitive and functional impairments had or developed major depressive episodes at or after the onset of cognitive impairment 47 or at baseline assessment. 48 A higher prevalence of depression has been reported among patients with vascular dementia or with mixed vascular dementia and Alzheimer disease.…”
Section: Co-occurring Depression and Cognitive Impairmentmentioning
confidence: 99%
“…In particular, depressive symptoms are common in older people with dementia in the form of Alzheimer's disease (AD) (Lyketsos and Olin 2002;Rubin et al 2001). Prevalence rates for depression are estimated at around 25 % for people with dementia (Ballard et al 1996) and 10-45 % for people with mild cognitive impairment (MCI) (Apostolova and Cummings 2008) compared with approximately 2 % in older adults aged 55 years and over and 65 years and over without cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%